PM DIRECTORY INTEGRATED ENVIRONMENT ANALYTICAL GEOMETRY COURSE FOR HIGHER EDUCATION - Yatsiuta, B.O.; Lvov, M.C.; Peschanenko, B.C. (Journal of Information Technologies in Education (ITE), 2009)
The work by PM Directory integrated environment Analytical Geometry course for higher education, show the properties of language Aplan and the possibility of its use to solve various problems associated with arithmetic calculations, conversion and parsing complicated expressions. From the perspective of software applications submitted language. Thoroughly reviewed mathematical kernel module directory ISA software Analytical Geometry. Displaying architecture and directory capabilities and examples of problems that may decide his help.